Moving Interfaces in Crystalline Solids - Fischer, Franz D.; Schmid, Erich (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2005)
Moving Interfaces in Solids are typically phase boundaries and grain or subgrain boundaries. Continuum thermodynamics and continuum mechanics are applied to explain the motion process. Related numerical and experimental concepts are dealt with. Experts from material physics and mechanics bridge the gap between these fields. The reader is offered a common view of interface mtion in a unique representation. Examples are presented for various material systems.